Design of an Axle Wheel Laboratory Tool Assisted by Phyphox to Enhance Students’ Critical Thinking Skills - Nurul Faizah; Anwaril Huda (Journal of Advances in Physics Education, 2026)
This research aims to develop a wheel-and-axle practicum apparatus assisted by the Phyphox sensor application to support the verification of mechanical advantage concepts and strengthen students’ critical thinking skills in rotational dynamics learning. The study employed the Research and Development (R&D) method with the 4D model, limited to the development stage due to time constraints. Product validation involved four expert validators, consisting of a physics content expert, a learning media expert, a sensor technology expert, and a pedagogical expert. Validation data were analyzed using Aiken’s V formula. The results indicate that the developed practicum tool meets the criteria of content accuracy, technical feasibility, safety, and pedagogical appropriateness. The overall Aiken’s V coefficient was 0.91, categorized as highly valid. Experts noted that the integration of magnetic sensors with the Phyphox application enables real-time measurement of angular velocity, providing more precise experimental data compared with manual stopwatch-based methods. The tool effectively visualizes rotational dynamics concepts—such as torque, moment of inertia, and angular acceleration—making it a suitable medium for inquiry-based physics learning. Thus, the Phyphox-assisted wheel-and-axle apparatus is feasible for implementation in physics practicum activities and has the potential to enhance students’ critical thinking skills.